HUBUNGAN KUALITAS INFORMASI AKUNTANSI KEUANGAN SYARIAH DENGAN KINERJA KEUANGAN BAITULMAL WATTAMWIL (BMT) DI KOTA MAKASSAR - Nurfaidah Nurfaidah (AkMen JURNAL ILMIAH, 2013)
This study empirically tested to determine he correlation between information quality of haria financial accounting consists of: relevance, reliability, comparable, consistent and understandable financial performance of BMT in Makassar. Target population was 25 BMT guided by Small Business Incubation Center (PINBUK) Makassar. In the implementation of 25 BMT that was only 13 BMT reported their activities actively in the form of financial statements, and who has complete financial statements just as much as 12 BMT, then the BMT-12 is being sampled in the study. The test results of partial correlation analysis with Spearman Rank correlation, suggesting that sharia financial accounting information quality has a positive and significant relationship with financial performance. The results of the analysis has indicated that the quality of each aspect of the quality of accounting information is better, Thus the financial performance of BMT will be better too. The results of multiple correlation testing by Kendall Concordance Correlation analysis of all aspects: reliability relevance, comparable, consistent, understandable financial performance, and significantly positively correlated with the very high category. Thus improving the quality offinancial accounting information will be followed by financial performance improvement.